Hospitalization costs for children younger than five years of age for gastroenteritis caused by rotavirus. Cienfuegos Pediatric Hospital, 2018 - Isel de los Ángeles Gázquez Altuna; Anai García Fariñas; Alain Rubén Reyes Sebasco; María Elena Quiñones Hernández; Martha de la Caridad Marrero Araújo; Isabel Pilar Luis Gonzálvez; Nivaldo Linares Pérez (Medisur)
Background: The study of the hospitalization costs for rotavirus gastroenteritis is a strategic issue given the dilemma of introducing or not a rotavirus vaccine in Cuba. Objective: to estimate the institutional cost of hospitalization of patients younger than five years of age because of gastroenteritis due to rotavirus. Methods: descriptive study, specifically a partial economic evaluation of the costs description type. Modeled cost per care protocol adjusted to standard practice was used. The normative documents were reviewed and an adjustment exercise was applied to routine practice by consulting experts. The cost was expressed in 2018 Cuban pesos. Results: admission to the Gastroenterology ward was estimated for 93.1% of the patients, of which 99.4% would solve the health problem. The salary was the item with the highest contribution to spending, although in the Gastroenterology ward it was the complementary examinations. The average cost of hospitalization modeled for rotavirus gastroenteritis was 435.13 Cuban pesos; this varied according to the clinical condition with which the patient arrives, between 415.72 pesos and 1057.60 pesos. The cost was sensitive to the variation of the stay in the services. Conclusion: Hospitalization of a patient younger than five years of age for gastroenteritis due to rotavirus represents high costs for the hospital. The attention service to critical patients and the previous admission to a clinical room other than that of Gastroenterology, increase the cost of care.